Victimological measures to prevent violent offences for gain committed by children - Shablystyi, Volodymyr; Kovalenko, Andriy; Hetman, Anastasiia; Kvasha, Roman (Cuestiones Políticas, 2020)
The aim of the article is to be a victimological description of violent crimes for profit by children in Ukraine. The research methodology was based on the equal combination of the legal method, logical and semantic method, comparative method, documentary, test method, classification method, method, and method of system analysis. Among the most notable results of the study were victims who contribute to the commission of crimes for profit and. Everything allows that, the theory of victimological modeling is a logical result of victim thought in criminology, which aims to be the models of the concluding victim of victims of crime crimes, etc.) in order to develop measures that are advised of the victim. The objectives of preventing lost crimes through the development and implementation of long-term state programmed for prevention. The implementation of these laundry programs a mechanism for the effective prevention of victims, the effectiveness of the fight against crime and will ensure safety.